PERBANDINGAN SISTEM AKAD ASURANSI JIWA SYARIAH DI INDONESIA DAN MALAYSIA: TINJAUAN REGULASI DAN IMPLEMENTASI - Rifqy, Eza; Purwanto, Purwanto; Suryani, Irma (Universitas Labuhanbatu, 2025)
This study aims to analyze and compare the system of sharia life insurance contracts in Indonesia and Malaysia, with a particular focus on regulation and implementation aspects. Sharia life insurance, as an alternative to conventional insurance, is based on Islamic principles that prohibit riba, gharar, and maysir. The research method applied is normative juridical with a comparative approach, through an analysis of legislation, fatwas, and the implementation practices of the sharia insurance industry in both countries. The findings indicate similarities such as the use of the tabarru’ contract and the separation of participants’ funds from company funds. However, differences arise in contract structures, regulatory frameworks, and forms of implementation, which are influenced by each country’s legal system. Malaysia is more advanced in establishing specific regulations and strengthening implementation through takaful, while Indonesia still faces limitations due to the absence of a specific law on sharia insurance. Therefore, this study recommends that Indonesia strengthen its legal framework by enacting a specific regulation on sharia insurance and updating the practice of sharia life insurance contracts to enhance legal certainty and participant protection.Keywords: Sharia Life Insurance, Comparison, Contract, Regulation, Implementation